SOUTHWESTERLY ENLARGEMENT OF GREATER CHINA - BELOKRINITSKIY, Viacheslav (CENTRAL ASIA AND THE CAUCASUS, 2007)
The beginning of the 21st century provided a new platform for viewing the relations be-tween the West and East in the world economy and politics. Three factors were largely conducive to this—the rapid economic upswing of China and India (two sleeping giants of the past century), the powerful upsurge in the demo-graphic potential of the Islamic world, and the demographic decline in the area where Western cultures are widespread, which caused a security crisis and gave rise to a nervous reaction in the West to the risks and challenges in this sphere. After becoming involved first in the Afghan, and then in the Iraqi war, the U.S. began to have doubts about the unconditional nature of its leadership in the world, thus giving China and other Asian states (beyond the Near and Middle East) time to catch their breath after the 1997-1998 crisis and show greater initiative in resolving the tasks they faced. One of the results of this reassessment of the situation is the idea of China’s growing “region-forming” role, which being the country with the largest population on the planet, is transforming before our very eyes into the largest world economy. It is a well-known fact that today’s economic progress is distinguished by high energy intensity. It is particularly high in the developing Asian economies, such as China and India. The PRC already occupies second place in the world (after the U.S.) in terms of energy consumption. Energy requirements are one of the reasons China is extremely interested in creating safe conditions for delivering the energy resources it needs to ensure invariable economic growth. There are doubtlessly other geo-economic and geopolitical factors explaining the PRC’s interest in forming and reinforcing regional security all along its borders. A.D. Voskresenskiy sees the increase in the Chinese factor and the country’s influence as the reason for the recent contraction of the traditional regions of Northeast, Southeast, South, and Central Asia into a single, interrelated East-Asian regional complex.1 The formation of Greater East Asia (or Greater China) is still in its infancy. Nevertheless, we should agree both with the analytical substantiation of the author’s conception, and with his assertion that such a large regional complex is based not so much on politico-ideo-logical preferences, although they are also important, as on ideas of security and objective patterns of the growing integration under globalization conditions of contiguous, but in the recent past rather isolated and topographically clearly designated, regions.